2011
DOI: 10.3174/ajnr.a2531
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Idiopathic Normal Pressure Hydrocephalus from Other Dementias Using Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:Because DTI can provide good markers of white matter pathology, it could be useful in differentiating white matter changes of INPH from those of other dementias. The aim of this study was, by using DTI, to compare the characteristic white matter changes in INPH with those in AD, subcortical vascular dementia, and healthy control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 31 publications
3
62
1
Order By: Relevance
“…This finding conflicts with previous studies that reported higher FA values within the corticospinal tracts for INPH patients than for normal subjects. 6,22) Such changes were even reversible after shunt implantation. 22) This could mean that higher corticospinal tract FA values may be important to better characterize INPH white matter changes.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This finding conflicts with previous studies that reported higher FA values within the corticospinal tracts for INPH patients than for normal subjects. 6,22) Such changes were even reversible after shunt implantation. 22) This could mean that higher corticospinal tract FA values may be important to better characterize INPH white matter changes.…”
Section: Discussionmentioning
confidence: 79%
“…6,22) Such changes were even reversible after shunt implantation. 22) This could mean that higher corticospinal tract FA values may be important to better characterize INPH white matter changes. Recently, DTI tractography showed that neural fibers in corticospinal tracts were compressed by ventricular dilation, resulting in higher FA values for INPH patients.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%